Customer Perception towards Mobile Banking Services in Kathmandu District - Vaibhav Karn (Journal of Corporate Finance Management and Banking System, 2024)
This study used quantitative methods to investigate how consumers perceive mobile banking services in the Kathmandu district. The research analyzed the impact of perceived ease of use, self-efficacy, perceived cost, trust, security, and perceived usefulness on the intention to use mobile banking services, surveying 213 participants. Data was collected through a self-structured questionnaire, and various statistical analyses, including descriptive statistics, correlation coefficients, regression analysis, and ANOVA, were employed to assess the relationships between intention to use mobile banking and the independent variables of perceived ease of use, self-efficacy, perceived cost, trust, security, and perceived usefulness. The data was processed using SPSS Statistical Package 25.